2019
DOI: 10.1177/1558944719844348
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Radial Artery Injuries: Variable Injury Patterns, Treatment Times, and Outcomes

Abstract: Background: The radial artery is commonly accessed for arterial blood sampling, invasive blood pressure monitoring, and vascular access for cardiac catheterization. Iatrogenic radial artery injury is a rare complication with potentially devastating outcomes. The purpose of our study was to identify the timing of these injuries and define a treatment algorithm. Methods: A retrospective chart review of all patients with iatrogenic radial artery injuries were identified between the years 2008 and 2018. Patient de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
0
12
0
1
Order By: Relevance
“…Digital ischemia. Insufficient flow of oxygenated blood to the digits with the risk of necrosis and subsequent iatrogenic or autoamputation (54)(55)(56).…”
Section: Radial Artery Occlusion Absence Of Radial Artery Patency Defined In the Prevention Of Radial Artery Occlusion-patent Hemostasis mentioning
confidence: 99%
“…Digital ischemia. Insufficient flow of oxygenated blood to the digits with the risk of necrosis and subsequent iatrogenic or autoamputation (54)(55)(56).…”
Section: Radial Artery Occlusion Absence Of Radial Artery Patency Defined In the Prevention Of Radial Artery Occlusion-patent Hemostasis mentioning
confidence: 99%
“…As a result, there is a chance that the incidence of RAT during TRI has been underestimated in previous studies. For example, data from ACUITY and SWITCH III trials showed that no device-associated thrombus could be documented under routine angiography [ 26 , 27 ]. Currently, OCT has shed light on the assessment of intravascular thrombus and evaluating efficacy of antithrombotic drugs in vivo [ 2 ], and it is reasonable that growing evidence for intraprocedure thrombosis will draw attention in the future.…”
Section: Discussionmentioning
confidence: 99%
“…48 Complications related to radial access are rare, but potentially devastating and include radial artery pseudoaneurysm formation or acute radial artery thrombosis with subsequent hand ischemia. 49 The role of the interventionalist in these settings is limited; treatment options following iatrogenic radial artery injury typically consist of anticoagulation and surgical intervention. 49 Errant placement of large bore (>7 Fr) central venous catheters is another common cause of iatrogenic arterial injury.…”
Section: Iatrogenic Injurymentioning
confidence: 99%
“…49 The role of the interventionalist in these settings is limited; treatment options following iatrogenic radial artery injury typically consist of anticoagulation and surgical intervention. 49 Errant placement of large bore (>7 Fr) central venous catheters is another common cause of iatrogenic arterial injury. Inadvertent placement of these catheters into arteries complicates 0.1 to 8% of attempted central line placements.…”
Section: Iatrogenic Injurymentioning
confidence: 99%